Instrument fracture in periodontal therapy: ethical disclosure and clinical management - a case report - Hassan Yaqoob; Ali Sadiq; Muhammad Karim; Syed Murtaza Raza Kazmi (BMC, 2024)
Abstract Periodontal instrument fractures are rare events in dentistry, with limited literature available on their occurrence and management. This case report highlights an incident involving the fracture of a periodontal sickle scaler blade during manual instrumentation for the removal of calculus. The fracture occurred during instrumentation on the mesial surface of the maxillary right second molar, and the separated blade was subsequently pushed into the sulcus. A radiographic assessment was performed to verify the precise location of the fractured segment. Following confirmation, the broken blade was subsequently retrieved using curved artery forceps. The case report highlights factors contributing to instrument fractures, emphasizing the importance of instrument maintenance, sterilization cycles, and operator technique. Ethical considerations regarding patient disclosure, informed consent, and instrument retrieval methods are well discussed. This case underscores the importance of truthful communication, the proper use of instruments, equipment maintenance in dentistry, and the significance of ongoing professional development to enhance treatment safety, proficiency, and ethical standards in dental care.